Five Keys to Caring for the Family-School Relationship (Journal of Parents and Teachers, 2026)
Education is a relational act. Based on this conviction, the family-school alliance is not a formality nor is it activated only when problems arise, but rather it sustains the climate, educational consistency and the comprehensive development of the student. In a context of diverse families and more demanding schools, the challenge is to cultivate trust and shared responsibility from the outset so that children and adolescents grow up accompanied by a community. Family and school united for the greater good of the child/student.
Keywords: family-school relationship; parent teacher cooperation; parent participation home school relationship; parent school relationship; conflict resolution